Telenursing-Based Self-Care Management Education Improves The Quality Of Life Of Hypertension Sufferers In The Rural Area Pragaan Health Center - Suprayitno, Emdat; Permatasari, Dian; Huzaimah, Nailiy (Interest : Jurnal Ilmu Kesehatan, 2023)
Background: A person's view of their life within the framework of their culture and values, which encompass the areas of physical, psychological, social, and environmental activities, is referred to as their quality of life. In order to raise awareness and promote self-care, intervention measures are desperately needed. The purpose of this research is to evaluate how telenursing education affects hypertension patients' quality of life.   Methods: This study used a quasi-experimental methodology. With a simple random sample, the population consisted of sixty hypertensive people. The sixty-person sample was split into two groups: thirty individuals in the treatment group got an educational intervention centered around supportive care, while thirty individuals in the control group were given hypertension pamphlets.   Results: The quality of life score in the treatment group following the intervention was p = 0.000, according to research based on the independent t-test. The study's findings demonstrated the effectiveness of telenursing instruction in raising hypertension patients' quality of life; as such, this intervention may catalyze raising hypertensive patients' levels of self-care.   Conclusion: In conclusion, telenursing education support has an impact on hypertension patients' quality of life.